Chronic thromboembolic pulmonary hypertension following long-term peripherally inserted central venous catheter use. (June 2019) - Masding, Abigail; Preston, Stephen D.; Toshner, Mark; Barnett, Joseph; Harries, Carl; Dimopoulos, Konstantinos; Kempny, Aleksander; McCabe, Colm; Jenkins, David P.; Wort, S. John; Price, Laura C.
A 36-year-old woman presented with recurrent pulmonary emboli (PE) despite oral anticoagulation. She was a type I diabetic with severe gastroparesis requiring insertion of multiple long-term peripherally inserted central catheters (PICC) over a 10-year period. Imaging at presentation demonstrated a PICC-associated mobile mass in the right atrium and signs of pulmonary hypertension (PH). She was thrombolyzed and fully anticoagulated, and diabetic management without PICC strongly recommended. PH persisted, however, and she developed chronic thromboembolic pulmonary hypertension (CTEPH), for which successful pulmonary endarterectomy (PEA) surgery led to symptomatic and hemodynamic improvement. This was the first case of CTEPH reported related to long-term PICC use outside the setting of malignant disease, and a novel observation that the PEA specimen contained multiple plastic fragments. Long-term PICC placement increases the risk of CTEPH, a life-threatening, albeit treatable, complication.